PENDAMPINGAN AKUNTANSI DAN PAJAK AMAL USAHA MUHAMMADIYAH (AUM) SE – KABUPATEN BOJONEGORO - Tumirin, Tumirin; Mujaddid, Abdullah; Hariyono, Anwar; Suwandi, Suwandi (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
The purpose of community service is to conduct training and assist in the preparation and preparation of financial and taxation reports at the Amal Usaha Muhammadiyah (AUM) throughout Bojonegoro Regency. The method of implementing the activity is to conduct training and face-to-face meetings by presenting presenters. The activity will be held on 31 October 2019. The training results show that there are still many institutions that have not prepared financial reports in accordance with generally accepted accounting standards. Most still use cash statements only. Financial personnel still need further assistance. Most tax reports have not yet been made and reported.